The Lean Project Approach to Anticipate Delays in the Construction of 3.5 GT Fishing Boats (Case Study at PT. X) - Hidayah, Asfarina (Universitas Merdeka Malang, 2023)
Projects generally have a deadline for completion. So far, PT. X often experiences delays in project completion. The problem is that waste often occurs in the production process. As a result, the company can suffer losses if waste m is not minimized immediately. The purpose of this research is to identify waste that contributes to delays in the construction of 3.5 GT fishing vessels and to increase the Value Stream by using the Lean Project methodology to estimate delays. Utilizing the Lean Project methodology, this research identifies and maps waste in every manufacturing step.The recommended value stream creation is based on the total time spent on each component, which is calculated from 18.7 hours to prepare the mould, 26.5 hours to manufacture the hull, 28 hours to assemble, 112 hours to manufacture the steering system, and 88 hours to manufacture the finish. The initial value stream for one unit of the Sumbawa 3.5 GT fishing vessel is 273 hours, or 34 days, according to the estimated time for each stage of the production process. The planned lead time is 678 hours or 84 days less than the previous lead time. The difference from the anticipated value stream is 405 hours or 51 days.